Pembentukan kader Posbindu di Wilayah Kelurahan Balecatur Gamping Sleman - Sri Arini Winarti Rinawati; Nur Hidayat (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
The Integrated Non-Communicable Disease Development Post (Posbindu PTM) is a form of promotive and preventive community participation in activities for early detection, monitoring, and early follow-up of PTM risk factors independently and continuously. This Community Service is carried out by forming PTM Posbindu cadres in the Balecatur Village area, Gamping, Sleman, Yogyakarta. In practice, this activity is divided into 3 meetings, namely coordination meetings, training, and evaluation monitoring. The activity went smoothly and was attended by 23 participants consisting of cadres, community leaders, religious leaders, and youth organizations. From this activity, participants have been appointed to be the management of the PTM Posbindu and are willing to hold the PTM Posbindu continuously and always coordinate with the Yogyakarta Gamping Health Center.